Implementasi Peraturan Menteri Perdagangan Nomor 06/M-DAG/PER/2015 - Harahap, Zulfa Rahmi (Jurnal El-Thawalib, 2021)
The focus of this research is on the implementation of the Regulation of the Minister of Trade Number 06 / M-Dag / Per / 2015 concerning the Regulation and Supervision of traditional alcoholic beverage tuak in Sipupus Village. The circulation of tuak drinks in Sipupus Village seems very free, and it seems that supervision is still lacking, even though it is clear that there are regulations governing this matter. The results of this study are that the implementation of Regulation of the Minister of Trade Number 06 / M-Dag / Per / 2015 concerning the Regulation and Control of Traditional Tuak Alcohol in Sipupus Village has not been implemented in accordance with the applicable provisions. tasks from the Sipupus Village Government or from the authorized service agency, namely the North Padang Lawas Industry and Trade Service. The inhibiting factor has not materialized the implementation of Regulation of the Minister of Trade Number 06 / M-Dag / Per / 2015 concerning the Regulation and Control of Traditional Tuak Alcoholic Drinks in Sipupus Village, namely the unclear status of traditional tuak alcoholic drinks, there is no firmness from the local government. Cultural factors where there are still strong customs in the village community